APOE ε4/ε4 diminishes neurotrophic function of human iPSC-derived astrocytes. (21st April 2017) - Zhao, Jing; Davis, Mary D.; Martens, Yuka A.; Shinohara, Mitsuru; Graff-Radford, Neill R.; Younkin, Steven G.; Wszolek, Zbigniew K.; Kanekiyo, Takahisa; Bu, Guojun
Abstract: The ε4 allele of the APOE gene encoding apolipoprotein E (apoE) is a strong genetic risk factor for aging-related cognitive decline as well as late-onset Alzheimer's disease (AD) compared to the common ε3 allele. In the central nervous system, apoE is produced primarily by astrocytes and functions in transporting lipids including cholesterol to support neuronal homeostasis and synaptic integrity. Although mouse models and corresponding primary cells have provided valuable tools for studying apoE isoform-dependent functions, recent studies have shown that human astrocytes have a distinct gene expression profile compare with rodent astrocytes. Human induced pluripotent stem cells (iPSCs) derived from individuals carrying specific gene variants or mutations provide an alternative cellular model more relevant to humans upon differentiation into specific cell types. Thus, we reprogramed human skin fibroblasts from cognitively normal individuals carrying APOE ε3/ε3 or ε4/ε4 genotype to iPSC clones and further differentiated them into neural progenitor cells and then astrocytes. We found that human iPSC-derived astrocytes secreted abundant apoE with apoE4 lipoprotein particles less lipidated compared to apoE3 particles. More importantly, human iPSC-derived astrocytes were capable of promoting neuronal survival and synaptogenesis when co-cultured with iPSC-derived neurons with APOE ε4/ε4 astrocytes less effective in supporting these neurotrophic functions than those with APOE ε3/ε3 genotype. Taken together, our findings demonstrate APOE genotype-dependent effects using human iPSC-derived astrocytes and provide novel evidence that the human iPSC-based model system is a strong tool to explore how apoE isoforms contribute to neurodegenerative diseases.